Development of Chitosan@ZnO@Ghassoul clay biohybrid beads for photocatalytic dye degradation and Cu(II) photoreduction - Soukaina El Bourachdi; Yassine Ballout; Ali Raza Ayub; Abdelhay El Amri; Yassine Rakcho; Mahdi Lechheb; Ilham Naghoum; Ilham Aichouch; Belkheir Hammouti; Mohamed Loutou; José Miguel Doña Rodriguez; José Alberto Herrera-Melián; et al. (Biomass and Bioenergy, 2027)

Divergent effects of a Bacillus biofertilizer immobilized in guinea pig manure biochar: Boosting productivity vs. enhancing nutritional quality in maca monocultures - Richard Solórzano; Ana Carranza-Ramirez; Nora Vera-Obando; Rosario Javier-Astete; Alberto Arias-Arredondo; Melina Lopez-Rodriguez; Michell K. Arroyo-Julca; Excela Saavedra-Flores; Cinthia Quispe-Apaza; Lizbeth Mamani-Rojas; Juancarlos Cruz; Angel Montes Osorio; et al. (Applied Soil Ecology, 2026)

Etiology of Chickpea Yellowing Syndrome (CYS) in Argentina: the role of fungal and viral pathogens - Bruno Daniel Pugliese; Patricia Rodriguez Pardina; Juan Pablo Edwards Molina; Sebastián Alberto Stenglein; Silvina Pastor (European Journal of Plant Pathology, 2026)

Correction: Etiology of Chickpea Yellowing Syndrome (CYS) in Argentina: the role of fungal and viral pathogens - Bruno Daniel Pugliese; Patricia Rodriguez Pardina; Juan Pablo Edwards Molina; Sebastián Alberto Stenglein; Silvina Pastor (European Journal of Plant Pathology, 2026)

Activation of Toll-like receptor 2 reveals microbial contamination beyond endotoxins on micro- and nanoplastics - Øyvind P. Haugen; Itziar Polanco-Garriz; Victor Alcolea-Rodriguez; Raquel Portela; Rita Bæra; Hamed Sadeghiankaffash; Jana Hildebrandt; Dmitri Ciornii; Korinna Altmann; Francesco Barbero; Ivana Fenoglio; Julián J. Reinosa; et al. (Toxicology in Vitro, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

A SAFER Model for Accurately Estimating Actual Evapotranspiration in Sugarcane Using Sentinel-2 - Alberto Mario Arroyo Avilez; Julian David Ome Narváez; Julian Fernando Mateus-Rodriguez (Sugar Tech, 2026)

AWARE historic and 2024 characterization factors for Spain - Iago Ferreiro-Crespo; Pedro Villanueva-Rey; Alberto Couce-Rodriguez; Carla Carreira-Garcia; Elena Robles; Yago Lorenzo-Toja; Gumersindo Feijoo (The International Journal of Life Cycle Assessment, 2026)
Purpose Water scarcity is a growing concern, especially in regions with Mediterranean, arid, and semi-arid climates. Conventional indicators often use historical data, limiting accuracy under current hydrological changes. This study aims to develop an improved methodology for water scarcity assessment in Spain, enhancing the AWARE approach by integrating current reservoirs data and refined demand estimates to increase spatial and temporal precision. Methods he AWARE-based methodology was adapted for Spain by incorporating up-to-date reservoir storage data and demand values sourced from official hydrological plans. The assessment operates at the granularity of Demand Units, the most resolved administrative partition in Spanish basin management, thereby permitting high-resolution spatial disaggregation. Characterization factors reflecting water scarcity were evaluated for each Demand Unit in annual time steps, superseding the static application of historical averages. This methodological refinement facilitates differentiated calculation of local water demand and supply, allowing a temporally dynamic and spatially resolved portrayal of water stress across the national territory. Results and discussion Application of this advanced methodology to 2024 data reveals an average increase of 8.3% in water scarcity characterization factors relative to historical baselines. However, this national mean conceals significant regional contrasts: certain regions experienced improved availability, while others exhibited intensified drought conditions, highlighting entrenched polarization in Spain’s hydrological landscape. The dynamic integration of supply and demand enhances the accuracy and adaptability of scarcity metrics compared to static approaches, facilitating improved identification of at-risk areas and underpinning environmental impact assessments with locally relevant evidence. Conclusions The developed methodology offers temporally responsive and spatially resolved water scarcity characterization factors tailored for the Spanish context, providing a robust tool for informed environmental assessments and sustainable regional water management. Given its modular and data-driven structure, this framework demonstrates strong potential for replication and adaptation in other regions facing similar hydrological challenges, contributing to the advancement of globally applicable water scarcity assessment practices.

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Characterization of different types of micellar casein isolates and comparison of their enzymatic coagulation behavior by chymosin and pepsin - Mengjia Li; Hugo Alberto Vigil Rodriguez; Søren Drud-Heydary Nielsen; Luiza Patrycja Morawska; Ann Bjørnshave; Per Torp Sangild; Nina Aagaard Poulsen; Lotte Bach Larsen (Food Research International, 2025)

Comparison of the efficacy of a biocompatible and a distillable solvent for pretreatment of mixed bioenergy feedstocks - Md Maksudur Rahman; Matteo Ceriani; Seontae Kim; Venkataramana R. Pidatala; Hemant Choudhary; Blake A. Simmons; John M. Gladden; Alberto Rodriguez (Biomass and Bioenergy, 2025)

Integrated Population Pharmacokinetic-pharmacodynamic Modeling of HIV Virus-host Infection Dynamics in Patients Undergoing Antiretroviral Monotherapy - Alberto Vegas Rodriguez; Nieves Velez de Mendizábal; Yanan Zheng; Jason T. Hindman; Ramesh Palaparthy; John Ling; Iñaki F. Trocóniz; Ana Ruíz-Garcia; Justin S. Feigelman (The AAPS Journal, 2025)
Chronic human immunodeficiency virus (HIV) infection continues to pose a major global health challenge, with an estimated 39.9 M cases and 1.3 M new infections per year. Up to 75%, of people with HIV (PWH) are currently being treated with antiretroviral therapy. The development of effective treatments for HIV requires a detailed understanding of the virus-host interaction. Often, mathematical models are used to inform this understanding as well as to characterize therapeutic response. This work aims to develop a single and fully identifiable population semi-mechanistic pharmacokinetic/pharmacodynamic (popPKPD) model integrating data (drug levels, CD4 + T cells and viral RNA) of five different antiretroviral (ARV) drugs administered in monotherapy: lenacapavir, bictegravir, tenofovir alafenamide, emtricitabine and elvitegravir. Data were obtained from six phase 1 clinical studies and model development was performed using NONMEM 7.5.1. The viral dynamics were best described by expanding the “basic” viral dynamics model with two more populations of infected cells: chronically and latently infected. Obtained death rates values of infected cells & virus were consistent with literature values. Population baseline HIV-RNA was estimated to be 43,460 copies/mL, with an IIV of 141%, the estimated baseline concentrations of CD4 + cells varied largely across the different cell types in the model: 410, 20, 7 and 7 cells/mL for uninfected, infected, chronic and latently infected cells, respectively. The popPKPD model was able to capture key aspects of viral dynamics, drug behaviour, and treatment response. The models developed will serve as a useful tool for further development and optimization of these HIV therapies, especially when evaluating multiple ARVs to be administered in a novel combination setting. Graphical Abstract

Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA YOLK) administered by parenteral or mucosal routes against Brucella ovis in rams - María Celeste Moran; Agostina Tammone Santos; Paula Dominguez; Lucila Moriones; María Victoria Nieto Farias; Laura Maté; Juan Agustín García; Tobias Kuhn; Fernando Alberto Paolicchi; María Andrea Fiorentino; Marcelo Gastón Rodriguez; Jorge Pablo García; et al. (Veterinary Immunology and Immunopathology, 2025)

Flexible feeding strategy for high-yield PHA bioprocessing in Cupriavidus necator H16 from anaerobically fermented industrial wastewater - Natalia Hernández-Herreros; Alberto Rodriguez; Virginia Rivero-Buceta; Antonia Rojas; M. Auxiliadora Prieto (Bioresource Technology, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Structural insights into ABA receptor agonists reveal critical features to optimize and design a broad-spectrum ABA signaling activator - Mar Bono; Cristian Mayordomo; Alberto Coego; Jonatan Illescas-Miranda; Maria Rivera-Moreno; Lourdes Infantes; Pablo López-Carracedo; Mayra Sanchez-Olvera; Constanza Martin-Vasquez; Gaston A. Pizzio; Javier Merino; Javier Forment; et al. (Molecular Plant, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Correction to: Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández‑Pérez; Joan Jiménez‑Balado; Adrià Macias‑Gómez; Antoni Suárez‑Pérez; Marta Vallverdú‑Prats; Alberto Pérez‑Giraldo; Marc Viles‑García; Julia Peris‑Subiza; Sergio Vidal‑Notari; Eva Giralt‑Steinhauer; Daniel Guisado‑Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

The nature-based solution implementation gap: A review of nature-based solution governance barriers and enablers - Juliette G.C. Martin; Anna Scolobig; JoAnne Linnerooth-Bayer; Jenan Irshaid; Julia J. Aguilera Rodriguez; Alberto Fresolone-Caparrós; Amy Oen (Journal of Environmental Management, 2025)

Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández-Pérez; Joan Jiménez-Balado; Adrià Macias-Gómez; Antoni Suárez‑Pérez; Marta Vallverdú-Prats; Alberto Pérez-Giraldo; Marc Viles-García; Julia Peris-Subiza; Sergio Vidal-Notari; Eva Giralt-Steinhauer; Daniel Guisado-Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Wastewater treatment and energy generation for dark fermentation bioreactor: preliminary results - Laura Estefania Vanegas; Lucia Andrea Hurtado; Karol Lucia Fuentes; Mario Alberto Escobar; Tatiana Rodriguez Chaparro (International Journal of Environmental Science and Technology, 2025)
H 2 is known as the main energy vector in the global energy transition. However, the use of fossil fuels for its production remains the most widely used primary source. Among the new alternatives for the organic production of H 2 , the Dark Fermentation process is an attractive technique since the raw material is residual biomass. H 2 is currently used for transport and fertilizer production. Hence, this study aims to evaluate the feasibility of producing electricity from H 2 produced in a Dark Fermentation process by treating synthetic wastewater in a packed bed bioreactor coupled with a fuel cell. The results showed that the maximum H 2 production rate and H 2 yield were 108 mL H 2 /h.L and 10.57 mol H 2 / mol, respectively; the maximal current value was ca. 13.7 mA for an active electrode area of 10 cm 2 ; and the higher tension was 1.3. Moreover, the Fuel Cell generated an average current of 3.12 mA for 55 h with a voltage of 210 mV. It can be concluded that dark fermentation promotes electricity generation. However, it is still necessary to develop storage techniques for H 2 to maintain the electricity generated continuously. Graphical abstract

Development of a generalized pseudo-continuous model for fluid dynamics in packed bed reactors with a low d t / d p - Alberto Hernandez-Aguirre; Roel Hernandez-Rodriguez; J. Alberto Ochoa-Tapia; Carlos O. Castillo-Araiza (Chemical Engineering Journal, 2025)

Green covers effectively increase arthropod biodiversity in orchards, even at high management intensity - Remco Ploeg; Alberto Rodriguez Ballesteros; Ignasi Bartomeus; David Kleijn; Jeroen Scheper; Elena Velado Alonso (Agriculture, Ecosystems & Environment, 2025)

Decoding lower-limb kinematic parameters during pedaling tasks using deep learning approaches and EEG - Cristian Felipe Blanco-Diaz; Cristian David Guerrero-Mendez; Rafhael Milanezi de Andrade; Claudine Badue; Alberto Ferreira De Souza; Denis Delisle-Rodriguez; Teodiano Bastos-Filho (Medical & Biological Engineering & Computing, 2024)

Cardiac alterations induced by Heloderma horridum horridum venom in rats: An experimental study with ECG analysis using a linear regression algorithm - Karla Isabel Vazquez-Gonzalez; Alberto Ochoa-Brust; Alejandrina Rodriguez-Hernandez; Hugo Ventura-Cisneros; Gisela Jareth Lino-Lopez; Rafael Barbosa-Valdovinos; Armando Rodriguez-Vazquez; Oscar F. Vazquez-Vuelvas; Ramon A. Felix; Juana M. Jiménez-Vargas; Valery Melnikov; Laura Leticia Valdez-Velazquez (Toxicon, 2024)

Sperm melatonin receptors, seminal plasma melatonin and semen freezability in goats - Alberto J. Cardenas-Padilla; Francisco Jimenez-Trejo; Marco Cerbon; Araceli Chavez-Garcia; Norma B. Cruz-Cano; Martin Martinez-Torres; Alicia Alcantar-Rodriguez; Alfredo Medrano (Theriogenology, 2024)

Decision-making in open carpooling programs: Perspectives of drivers versus passengers - Willis Simancas; Cristian Vinasco; Daniel Rosas-Satizábal; Hernan Alberto Ortiz-Ramirez; Alvaro Rodriguez-Valencia (Travel Behaviour and Society, 2024)

Correction: Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2024)

Detection of pathogenic Leptospira spp. in unconventional pets - Bruna Carolina Ulsenheimer; Matheus Yuri dos Santos; Bruna Della Flora; Diego Andres Rodriguez Matarrita; Sônia de Avila Botton; Ana Eucares Von Laer; Daniela Isabel Brayer Pereira; Rafael Almeida Fighera; Alexandre Alberto Tonin (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Kinematics, intensity, and spatial arrangement of extensional fractures in the Tuxtla-Malpaso fault system: Chiapas strike-slip fault province, southern Mexico - Alberto Vásquez Serrano; María Fernanda Sampayo Rodriguez; Elisa Fitz Díaz; Gustavo Tolson (Journal of Structural Geology, 2024)

Multi-omic characterization of mechanisms contributing to rapid phenotypic plasticity in the coral Acropora cervicornis under divergent environments - Javier A. Rodriguez-Casariego; Alex Mercado-Molina; Leila Soledade Lemos; Natalia Soares Quinete; Anthony Bellantuono; Mauricio Rodriguez-Lanetty; Alberto Sabat; Jose M. Eirin-Lopez (Coral Reefs, 2024)

Bottom fishing beyond trawling. Spatio-temporal trends of mobile and static bottom fisheries on benthic habitats - Ulla Fernandez-Arcaya; Augusto Rodríguez-Basalo; Patricia Verísimo; José Rodriguez; Elvira Ceballos; Jose Manuel Gonzalez-Irusta; Ana García-Alegre; Maider Plaza-Morlote; Alberto Serrano; Antonio Punzón (Marine Policy, 2024)

Self-governance mediates small-scale fishing strategies, vulnerability and adaptive response - Timothy H. Frawley; Blanca González-Mon; Mateja Nenadovic; Fiona Gladstone; Keiko Nomura; José Alberto Zepeda-Domínguez; Salvador Rodriguez-Van Dyck; Erica M. Ferrer; Jorge Torre; Fiorenza Micheli; Heather M. Leslie; Xavier Basurto (Global Environmental Change, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Shelf life estimation of refrigerated vacuum packed beef accounting for uncertainty - Magdevis Y. Rodriguez-Caturla; Alberto Garre; Carmen Josefina Contreras Castillo; Marcel H. Zwietering; Heidy M.W. den Besten; Anderson S. SantˈAna (International Journal of Food Microbiology, 2023)

Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2023)
Purpose This study aims to develop and evaluate a cost-effective, user-friendly multiplex quantitative real-time polymerase chain reaction (qPCR) method for detecting multiple tick-borne pathogens associated with human and veterinary diseases. Methods In silico PCR was performed to design and evaluate primer sequences reported for amplifying Rickettsia spp ., Borrelia spp. , and Ehrlichia spp. Single and multiplex qPCR assays were then standardized to detect individual pathogens and multiple pathogens in a single reaction. Positive controls were generated to determine the dynamic range of the methods. In the validation phase, a total of 800 samples were screened for the presence of tick-borne pathogens. Results Identification in a single qPCR reaction (multiplex) of Ehrlichia spp . , and Borrelia spp. with a limit of detection of 10 copies and Rickettsia spp . with 100 copies, a PCR efficiency (E) of 90–100% and a coefficient of correlation ( R 2 ) of 0.998–0.996 for all pathogens. Conclusion The ability to detect three significant pathogens (Ehrlichia spp ., Rickettsia spp ., and Borrelia spp .) in a single qPCR reaction offers a significant advantage in the field of molecular diagnostics for tick-borne diseases. This advancement has a profound impact on public health as it facilitates the selection of appropriate treatment protocols, thereby reducing complications associated with disease progression. The streamlined approach provided by this method simplifies the diagnostic process and enables timely intervention, ultimately improving patient outcomes and mitigating the potential risks associated with untreated or misdiagnosed tick-borne infections.

Metals and metalloids in high-altitude Pyrenean lakes: sources and distribution in pre-industrial and modern sediments - Azibar Rodriguez-Iruretagoiena; Ainara Gredilla; Silvia Fdez-Ortiz de Vallejuelo; Gorka Arana; Maite Meaurio; Juan Manuel Madariaga; Jean Christophe Auguet; Aridane González González; Oleg S. Pokrovsky; Luis Camarero; Alberto de Diego (Environmental Science and Pollution Research, 2023)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.

Chronic H3R activation reduces L-Dopa-induced dyskinesia, normalizes cortical GABA and glutamate levels, and increases striatal dopamine D1R mRNA expression in 6-hydroxydopamine-lesioned male rats - Alberto Avila-Luna; Arturo Gálvez-Rosas; Alexander Aguirre-Pérez; Alberto Hidalgo-Bravo; Alfonso Alfaro-Rodriguez; Camilo Ríos; José-Antonio Arias-Montaño; Antonio Bueno-Nava (Psychopharmacology, 2023)

Variable response of Red Sea coral communities to recent disturbance events along a latitudinal gradient - Nicholas M. Hammerman; Alberto Rodriguez-Ramirez; Timothy L. Staples; Thomas M. DeCarlo; Vincent Saderne; George Roff; Nicole Leonard; Jian-xin Zhao; Susann Rossbach; Michelle N. Havlik; Carlos M. Duarte; John M. Pandolfi (Marine Biology, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

Regional wind pattern, a basis for defining the appropriate lapse of time for sugarcane burning in the Cauca Valley (Colombia) - Mónica Preciado Vargas; Héctor Alberto Chica Ramirez; Efraín Solarte Rodriguez; Javier Alí Carbonell Gonzalez; Andrés Javier Peña Quiñones (Environment, Development and Sustainability, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Ageusia and anosmia, a common sign of COVID-19? A case series from four countries - Jair Vargas-Gandica; Daniel Winter; Rainer Schnippe; Andrea G. Rodriguez-Morales; Johana Mondragon; Juan Pablo Escalera-Antezana; María del Pilar Trelles-Thorne; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales; Alberto Paniz-Mondolfi (Journal of NeuroVirology, 2020)

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

Pelagic Sargassum spp. capture CO2 and produce calcite - Francisco Paraguay-Delgado; Caleb Carreño-Gallardo; Ivanovich Estrada-Guel; Alberto Zabala-Arceo; Harby Alexander Martinez-Rodriguez; Daniel Lardizábal-Gutierrez (Environmental Science and Pollution Research, 2020)

A game theory model to explore the role of cooperation and diversity in community food security: the case of Southern Malawi - Stefano Balbi; Unai Alvarez-Rodriguez; Vito Latora; Alberto Antonioni; Ferdinando Villa (Regional Environmental Change, 2020)

A 3D-Fluorescence Fingerprinting Approach to Detect Physiological Modifications Induced by Pesticide Poisoning in Apis mellifera: A Preliminary Study - Christophe B. Y. Cordella; Alberto Izquierdo-Rodriguez; Marie-José Durand-Thouand (Journal of Fluorescence, 2019)

Potentiation of the first and second phases of the M wave after maximal voluntary contractions in the biceps brachii muscle - Javier Rodriguez-Falces; Taian Vieira; Nicolas Place; Alberto Botter (Medical & Biological Engineering & Computing, 2019)

On the Modeling of Patient-Specific Transcatheter Aortic Valve Replacement: A Fluid–Structure Interaction Approach - Giulia Luraghi; Francesco Migliavacca; Alberto García-González; Claudio Chiastra; Alexia Rossi; Davide Cao; Giulio Stefanini; Jose Felix Rodriguez Matas (Cardiovascular Engineering and Technology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Development of Chitosan and Alginate Nanocapsules to Increase the Solubility, Permeability and Stability of Curcumin - Daniel Hernandez-Patlan; Bruno Solis-Cruz; Mario Alberto Cano-Vega; Eric Beyssac; Ghislain Garrait; Xochitl Hernandez-Velasco; Raquel Lopez-Arellano; Guillermo Tellez; Gustavo R. Rivera-Rodriguez (Journal of Pharmaceutical Innovation, 2019)

Climate Change and Atlantic Multidecadal Oscillation as Drivers of Recent Declines in Coral Growth Rates in the Southwestern Caribbean - Luis D. Lizcano-Sandoval; Ángela Marulanda-Gómez; Mateo López-Victoria; Alberto Rodriguez-Ramirez (Frontiers in Marine Science, 2019)

Trophic ecology of European hake (Merlucius merlucius) larvae by stable isotopes analysis influenced by seasonal variability of oceanographic conditions off NW Galician waters. - Raul Carrion; Agueda Rodriguez; Jos M. Ervas; Alma De Rojas; Jose Maria Lopez; Piñeiro Carmen; Alberto Garcia (Frontiers in Marine Science, 2019)

Seasonal growth variability of young of the year European hake (Merluccius merluccius) off NW Spanish waters - Piñeiro Carmen; Lorena Fernandez; Jose Hervas; Agueda Rodriguez; Alberto Garcia (Frontiers in Marine Science, 2019)

Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.

Ocular flutter following Zika virus infection - Emely Karam; Jose Giraldo; Flor Rodriguez; Carlos E. Hernandez-Pereira; Alfonso J. Rodriguez-Morales; Gabriela M. Blohm; Alberto E. Paniz-Mondolfi (Journal of NeuroVirology, 2017)

The functional connectivity in the motor loop of human basal ganglia - Clara Rodriguez-Sabate; Magdalena Sabate; Catalina Llanos; Ingrid Morales; Alberto Sanchez; Manuel Rodriguez (Brain Imaging and Behavior, 2017)

Metabolic and transcriptional response of Escherichia coli with a NADP+-dependent glyceraldehyde 3-phosphate dehydrogenase from Streptococcus mutans - Sara Centeno-Leija; José Utrilla; Noemí Flores; Alberto Rodriguez; Guillermo Gosset; Alfredo Martinez (Antonie van Leeuwenhoek, 2013)

First Report of Microcystins and Anatoxin-a Co-occurrence in San Roque Reservoir (Córdoba, Argentina) - Marcia Ruiz; Lucas Galanti; Ana Laura Ruibal; María Ines Rodriguez; Daniel Alberto Wunderlin; María Valeria Amé (Water, Air, & Soil Pollution, 2013)

Testing for hybridization and assessing genetic diversity in Morelet’s crocodile (Crocodylus moreletii) populations from central Veracruz - Ricardo González-Trujillo; David Rodriguez; Alberto González-Romero; Michael R. J. Forstner; Llewellyn D. Densmore III; Víctor Hugo Reynoso (Conservation Genetics, 2012)

A novel amino acid substitution in the para-sodium channel gene in Rhipicephalus microplus (Acari: Ixodidae) associated with knockdown resistance - Marcelino Aguirre; Adriana E. Flores; Genoveva Álvarez; Alberto Molina; Iram Rodriguez; Gustavo Ponce (Experimental and Applied Acarology, 2010)

Potentiation of Local Anesthetic Activity of Neosaxitoxin with Bupivacaine or Epinephrine: Development of a Long-Acting Pain Blocker - Alberto J. Rodriguez-Navarro; Marcelo Lagos; Cristian Figueroa; Carlos Garcia; Pedro Recabal; Pamela Silva; Veronica Iglesias; Nestor Lagos (Neurotoxicity Research, 2009)

Response on the Comment on “Kinetics of the reactions of Cl atoms with 2-buten-1-ol, 2-methyl-2-propen-1-ol, and 3-methyl-2-buten-1-ol as a function of temperature” by Rodriguez et al. (J. Atmos. Chem. (2008) 59:187–197) - Diana Rodriguez; Ana Rodriguez; Amparo Soto; Alfonso Aranda; Yolanda Diaz-de-Mera; Alberto Notario (Journal of Atmospheric Chemistry, 2009)

Kinetics of the reactions of Cl atoms with 2-buten-1-ol, 2-methyl-2-propen-1-ol, and 3-methyl-2-buten-1-ol as a function of temperature - Diana Rodriguez; Ana Rodriguez; Amparo Soto; Alfonso Aranda; Yolanda Diaz-de-Mera; Alberto Notario (Journal of Atmospheric Chemistry, 2008)

Cellular target of helminthosporium sacchari Toxin in sugarcane tissue - Miguel Ramos-Leal; Alberto Ruiz; Rodolfo H. Maribona; Mayra Rodriguez; Eduardo Canales; Odelsa Ancheta; Orlando Coto (Sugar Tech, 2005)

Can machines recognise stress in plants? - Ronald Maldonado-Rodriguez; Stancho Pavlov; Alberto Gonzalez; Abdallah Oukarroum; Reto J. Strasser (Environmental Chemistry Letters, 2003)

Comparison of methods for sample preparation of individual rat cerebrospinal fluid samples prior to two-dimensional polyacrylamide gel electrophoresis - Sonia Garcia-Rodriguez; Sandro Argüelles Castilla; Alberto Machado; Antonio Ayala (Biotechnology Letters, 2003)

Sequence and diversity of MHC DQA and DQB genes of the owl monkey Aotus nancymaae - Diana Diaz; Martin Naegeli; Raul Rodriguez; J. Javier Nino-Vasquez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

Sequence and diversity of DRB genes of Aotus nancymaae , a primate model for human malaria parasites - J. Javier Nino-Vasquez; Denise Vogel; Raul Rodriguez; Alberto Moreno; Manuel Elkin Patarroyo; Gerd Pluschke; Claudia A. Daubenberger (Immunogenetics, 2000)

Sequence and diversity of T-cell receptor β-chain V and J genes of the owl monkey Aotus nancymaae - William Vecino; Claudia Daubenberger; Raul Rodriguez; Alberto Moreno; Manuel Patarroyo; Gerd Pluschke (Immunogenetics, 1999)

A novel germline mutation in exon 5 of the multiple endocrine neoplasia type 1 gene - A. Chico; Luis Gallart; Eugenia Mato; Carmen Mayoral; Jesus M. Martin-Campos; Lluís Catasús; Jose Rodriguez-Espinosa; Xavier Matías-Guiu; Francisco Blanco-Vaca; Alberto de Leiva (Journal of Molecular Medicine, 1998)